Profile of DHX37 gene defects in human genetic diseases: 46,XY disorders of sex development - Peng, Huifang; Peng, Wenyuan; Chen, Jiali; Hu, Keyan; Zhang, Yingyu; Ma, Yujin; Jiang, Hongwei (Frontiers in Endocrinology, 2025)
The RNA helicase DHX37 gene is involved in ribosomal biological processes, and linked to human genetic diseases associated with 46,XY disorders of sex development (46,XY DSD) or neurodevelopment. Recently, relevant reports have primarily focused on 46,XY DSD. However, there is still a lack of overall understanding of the genetic characteristics, phenotype, etc. of the DHX37 gene in human genetic diseases, and its molecular mechanism is not fully understood. We searched literature databases and summarized and analyzed all the literature related to DHX37 to date, including case reports, cohort studies, and molecular mechanism studies, to comprehensively demonstrate the role of DHX37 in human genetic diseases. Sixty patients were reported to have DHX37-related 46,XY DSD, with p.R308Q, p.R674W variants being the two most common mutation hotspots, accounting for 36.67% and 11.67% of cases respectively. In DSD cohorts, DHX37 gene mutations have different detection frequencies (0.77%–45.45%), whereas in testicular regression syndrome and 46,XY gonadal dysgenesis cohorts, they have a high detection rate. The gonadal development and fertility of female (46,XX) carriers with DHX37 gene mutations are not affected; however, incomplete penetrance may be observed in males (46,XY). The treatments are primarily surgical intervention and hormone replacement therapy administered at appropriate times; however, the long-term prognosis remains unknown. Although the molecular mechanism of DHX37 mutation related 46,XY DSD is unclear, ribosome synthesis, cell cycle regulation, and the NF-κB and Wnt pathways may be affected. This review summarizes the profile of DHX37 defects in human genetic diseases.